"Suffered and thrown away". Migrations, care and emotions in the fruit and vegetable sector of General Pueyrredon, Argentina (Quinto Sol, 2023)
Migration from Bolivia to Argentina is characterised by its family nature, and the jobs in which migrants are inserted –fruit and vegetable chains, brick kilns, textile workshops, street vending, etc.– usually involve the overlapping of domestic and market work spaces. As a result, women take on caregiving tasks while carrying out paid work, which means that caregiving has specific characteristics and involves specific emotional experiences. Although studies on Bolivian migration to Argentina are prolific, they have not focused either on the overlapping of spaces mentioned above or on the emotions that migration arouses. Taking horticulture as a case study and using a qualitative approach based mainly on interviews and participant observation, this article analysed the care work carried out by Bolivian women in Argentina. The focus was on their emotional experiences and those of the children in their care. As will be seen below, what mothers believed their children had felt as raised in the horticulture framework defined, to a large extent, their own emotional experiences.
Keywords: care; migrations; horticulture; emotions